Effects of Dietary Addition of a Low-Pectin Apple Fibre Preparation on Rats - Fotschki Bartosz; Jurgoński Adam; Juśkiewicz Jerzy; Kołodziejczyk Krzysztof; Sójka Michał (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to scrutinise if the dietary addition of a low-pectin fibre preparation obtained from apple pomace, the by-product of apple concentrate processing, is able to favourably affect the gut metabolism, antioxidant status and blood bio-markers of the organism, as it takes place when apple fibre is present in the diet as an unprocessed ingredient. The nutritional experiment was performed on rats allocated to 2 groups of 10 animals each and fed for 2 weeks with either a control cellulose-containing diet or an experimental low-pectin apple fibre-containing diet. To induce metabolic disorders a diet rich in saturated fat and fructose was used in both diet-specific groups. The dietary apple fibre preparation (AFP) significantly reduced the activity of sucrase and maltase in the mucosa of the small intestine. In the caecal digesta, the dietary AFP significantly increased bacterial α-glucosidase and α-galactosidase activity, whereas bacterial β-glucuronidase activity was significantly reduced. Also, the content of short chain fatty acids in the caecal digesta was significantly increased after the AFP supplementation. In the blood serum, the dietary AFP significantly reduced the glucose concentration, and decreased the ratio of total cholesterol to HDL cholesterol. In conclusion, the tested dietary AFP is still able to favourably affect the gut metabolism and can also ameliorate blood glucose concentration, which seems to be related to the inhibition of mucosal disaccharidase activities. However, the analysed preparation has no influence on the antioxidant status of the organism and may trigger adverse effects on cholesterol metabolism.